Urgensi Penyusunan Perencanaan Assesment Perkembangan Anak Usia Dini - Sugianto, Deby Sandra; Winengsih, Desy Rahayu; Syafitri, Amaliah; Oktavia, Dinda Tri; Ariyanto, Kharisma Kanjeng (JECED : Journal of Early Childhood Education and Development, 2023)
Early childhood development assessment planning is an essential component in efforts to ensure optimal child growth and development. This article examines the importance of preparing early childhood development assessment plans with a focus on identifying needs, effective assessment methods, and implementing appropriate strategies. Through a qualitative approach and literature analysis, this research reveals that careful and systematic planning is able to detect potential developmental problems early, so that intervention can be carried out early and on target. The results of this study show that good assessment planning is not only beneficial for children, but also supports parents and educators in understanding and facilitating children's development holistically. These findings emphasize the urgency of collaboration between various related parties to develop a comprehensive and sustainable assessment framework.